An extended comparative analysis using vignettes of dental care coverage. (30th September 2020) - Fattore, G; Winkelmann, J; Panteli, D; Allin, S
Abstract: Background: Virtually all European countries state to guarantee universal healthcare coverage to their citizens. However, there is evidence, although scarce, that dental care is a special case as coverage is very limited in some countries and there are major differences across national jurisdictions. This comparative study tries to better understand how dental care is covered in Europe and Canada through the use of five vignettes presenting dental services for specific patients. Methods: Experts from each country were asked to state whether the following situations were covered by their statutory systems: a) scaling and polishing to remove plaque deposits and calculus for an adult; b) treatment for caries including fillings and root canal treatment for an adult; c) prosthetic rehabilitation for an elderly; d) fillings and repairs for a seven-year old girl with serious tooth decay; e) orthodontic treatment for a 13 old boy. Results: Preliminary analysis of the vignettes from 10 countries show that there is a large variation between countries in who delivers dental care, how much it costs and who pays for it. Conclusions: Full coverage of dental care is rare in Europe and the extent of coverage varies greatly across countries in Europe and also in comparison to Canada.